Recent developments in functional and structural imaging of aphasia recovery after stroke - Meinzer, Marcus (2011)
BACKGROUND: Functional and structural neuroimaging techniques can increase our knowledge about the neural processes underlying recovery from post-stroke language impairments (aphasia). AIMS: In the present review we highlight recent developments in neuroimaging research of aphasia recovery. MAIN CONTRIBUTION: We review (a) cross-sectional findings in aphasia with regard to local brain functions and functional connectivity, (b) structural and functional imaging findings using longitudinal (intervention) paradigms, (c) new adjunct treatments that are guided by functional imaging techniques (e.g., electrical brain stimulation) and (d) studies related to the prognosis of language recovery and treatment responsiveness after stroke. CONCLUSIONS: More recent developments in data acquisition and analysis foster better understanding and more realistic modelling of the neural substrates of language recovery after stroke. Moreover, the combination of different neuroimaging protocols can provide converging evidence for neuroplastic brain remodelling during spontaneous and treatment-induced recovery. Researchers are also beginning to use sophisticated imaging analyses to improve accuracy of prognosis, which may eventually improve patient care by allowing for more efficient treatment planning. Brain stimulation techniques offer a new and exciting way to improve the recovery potential after stroke.